Investigating the effect of organizational culture on competitive advantage with mediating role of knowledge sharing and organizational innovation in agricultural cooperative companies of Golestan province - Eesa Niazi; Ramin Bagheri; Mirmohammad Mir (تعاون و کشاورزی, 2023)
Context and purpose. In order to know or predict how an organization will behave in different situations, one must know and understand the basic patterns of the organization's assumptions, i.e. its organizational culture. This research was conducted with the aim of investigating the effect of organizational culture on competitive advantage with the mediating role of knowledge sharing and organizational innovation in agricultural cooperative companies of Golestan province.Methodology/approach. The statistical population of this research includes all managers of agricultural cooperatives in Golestan province (300 people). The sample size was estimated to be 169 people according to the Krejcie-Morgan table, who were selected by simple random sampling method. To analyze the data, structural equation modeling technique by partial least squares method was used.Findings and conclusions. The results of data analysis show that in Agricultural Cooperatives, there is a significant relationship between organizational culture and competitive advantage due to the role of knowledge sharing and innovation, as well as between sharing knowledge and organizational innovation with competitive advantage. Originality. In this research, the effect of organizational culture on organizational innovation has been considered according to the mediating role of the two variables of knowledge sharing and organizational innovation, and in none of the previous researches, the mediating variables of knowledge sharing and organizational innovation have been considered.